2016
DOI: 10.1371/journal.pone.0159926
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis for Subjective and Objective Evaluations of Dental Drill Sounds

Abstract: The sound produced by a dental air turbine handpiece (dental drill) can markedly influence the sound environment in a dental clinic. Indeed, many patients report that the sound of a dental drill elicits an unpleasant feeling. Although several manufacturers have attempted to reduce the sound pressure levels produced by dental drills during idling based on ISO 14457, the sound emitted by such drills under active drilling conditions may negatively influence the dental clinic sound environment. The physical metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Concerns have been raised about hearing impairment to dentist from dental air turbine noise, and there have been numerous articles reporting an association between dental air turbine noise and hearing damage [ 6 – 9 ]. After reviewing 17 articles that assessed noise level in dental environments, Henneberry et al warned oral health professionals of potential hearing loss due to exposure to excessive noise limits (85 dBA) [ 10 ]. It has also been reported that the noise of a dental air turbine can cause fear and anxiety in patients [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised about hearing impairment to dentist from dental air turbine noise, and there have been numerous articles reporting an association between dental air turbine noise and hearing damage [ 6 – 9 ]. After reviewing 17 articles that assessed noise level in dental environments, Henneberry et al warned oral health professionals of potential hearing loss due to exposure to excessive noise limits (85 dBA) [ 10 ]. It has also been reported that the noise of a dental air turbine can cause fear and anxiety in patients [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Misuse of these tools can result in excessive or inadequate preparation and potential injury to the gingiva, tongue, and buccal and labial mucosa. Additionally, high-speed dental turbines generate vibrations and sharp noises, which can make patients uncomfortable [ 1 , 2 , 3 , 4 , 5 ]. Furthermore, the currently used laser and dental turbines may stimulate the dental pulp, which can lead patients to endure varying degrees of pain [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a subjective experience and is a symptom that undermines the patient's physical and mental integrity; moreover, it is closely related to fear, which is the individual's response to a threatening event. Dental anxiety is regarded as a serious health issue worldwide [ 7 ]. A dental phobia is a persistent and excessive fear of dental stimuli and procedures that results in avoidance or significant distress with impact on individual's normal routine, social relationships, occupational or school functioning, and social relationships [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in the literature have shown that the perceived pain was less when chemo-mechanical removal agents were used to remove caries compared to conventional rotary tools [ 18 ]. In other studies, it has emerged that chemo-mechanical caries removal agents have a very slow action compared to mechanical tools; moreover, it seems that they can be used together to completely remove the carious lesion tissue [ 7 ]. It has also emerged that the taste and odour of these used agents based on sodium hypochlorite were unpleasant [ 19 ].…”
Section: Introductionmentioning
confidence: 99%